Development of plasticized poly (vinyl chloride)/reduced graphene oxide nanocomposites for energy storage applications. (February 2019) - Akhina, H.; Mohammed Arif, P.; Gopinathan Nair, M.R.; Nandakumar, K.; Thomas, Sabu
Abstract: As the ever rising world population has led to increasing energy demand, it is necessary to develop efficient materials for energy storage applications. The enhancement of dielectric permittivity plays a significant role for designing materials for energy storage applications. Hence, composites with high dielectric permittivity are presently getting interest in academic and industrial research fields. In the present study, reduced graphene oxide (RGO) was compounded with plasticized poly (vinyl chloride) to obtain flexible composites which show both high dielectric permittivity and low dielectric loss. An enhancement of 57% in dielectric constant was obtained after the addition of RGO to poly (vinyl chloride). This enhancement can be attributed to the increased number of interfaces of polymer and filler that was observed by transmission electron microscopy. The interfacial polarization in the heterogeneous interface plays an important role in imparting dielectric performance. Effective dielectric permittivity values of the composites calculated using theoretical equations were found to be lower than the experimental values. The nanocomposites were also tested for the permeability of O2 which is very important for fabrication of energy storage devices. The permeability was decreased by 53% when compared to pristine poly (vinyl chloride). Hence, the enhanced dielectric permittivity as well as the impermeability to oxygen makes this material a suitable candidate for energy storage applications. Graphical abstract: Image 1 Highlights: Flexible nanocomposites based on cheap commodity plastic. Dielectric properties are investigated in arrange of frequencies (1000 Hz-30 MHz). Improved gas barrier properties. Micro structure correlated dielectric properties.